A smartphone application for reporting symptoms in adults with cystic fibrosis: Protocol of a randomised controlled trial - Wood, J.; Jenkins, Susan; Putrino, D.; Mulrennan, S.; Morey, S.; Cecins, N.; Hill, Kylie (BM J Group, 2018)
Introduction: In people with cystic fibrosis (CF), exacerbations have been shown to have profound and prolonged negative effects such as reducing physical activity and health-related quality of life, increasing the rate of decline of lung function and healthcare costs, and ultimately increasing the risk of mortality. Delayed initiation of treatment following the signs of an exacerbation has been shown to be associated with failure to recover to baseline. Therefore, the late identification and treatment of an exacerbation due to delayed presentation will potentially worsen short-term and long-term outcomes. We have developed a smartphone application, containing questions which require yes or no responses relating to symptoms suggestive of a respiratory exacerbation. Its use is intended to facilitate the early identification of symptoms suggestive of a respiratory exacerbation, and allow the CF team to initiate treatment sooner, thereby potentially reducing the risk of severe exacerbations which require intravenous antibiotics (IVAB) and often a hospital admission. Methods: We will undertake a randomised controlled trial. 60 adults with CF will be recruited and randomised to either the intervention or control group. The intervention group will use the smartphone application weekly for 12 months, or earlier than the next weekly reporting time if they feel their symptoms have worsened. The control group will continue to receive usual care, involving regular (approximately 3 monthly) CF outpatient clinic appointments. The primary outcome measure will be courses and days of IVAB. Ethics and dissemination: Approval was obtained from the Sir Charles Gairdner Group Human Research Ethics Committee for WA Health (2015-030) and Curtin University Human Research Ethics Committee (HR212/2015), and has been registered with the Australian and New Zealand Clinical Trials Registry. Results: of this study will be presented at international conferences and published in peer-reviewed journals in accordance with the Consolidated Standards of Reporting Trials statement. Trial registration number ACTRN12615000599572.